Decolorization and filter aid effect of silicon-magnesium mixed decolorizer in anchovy oil - LI Wen; YU Jun; XIE Chenwei; TAO Ningping (Shipin yu jixie, 2023)
Objective: This study aimed to improve the separation efficiency of decolorizing agent and fish oil, and ensure high decolorization rate at the same time. Methods: The optimum absorption wavelength of fish oil was measured by spectrophotometer. Magnesium silicate was mixed with activated clay into compound decolorizers, and was used to evaluate the decolorization rate and filtration speed. The decolorization parameters of anchovy oil were optimized by single factor experiment and response surface experiment. The oil absorption rate and fish oil recovery rate of decolorizing agent were calculated. The decolorization and filter aid effect of decolorizing agent were verified through the plate and frame filter scale-up experiment. Fatty acid absolute content of crude oil, degummed oil, deacidified oil, and bleached oil was determined by gas chromatography. Results: The best absorption wavelength of anchovy oil was 671 nm. The compound results of mixed decolorizer was as follows: the ratio of activated clay∶magnesium silicate was 4∶1 and its filtration rate was (26.65±0.64) mL/min. Response surface optimization results showed that the decolorization rate was (95.74±1.35)%, at the dosage of 5.0%, 57 min, and 72 ℃. The oil absorption rate was (1.15±0.10)% and fish oil recovery was (91.72±1.60)%. In the plate and frame filtration experiment, the decolorization effect of the mixed decolorizer was not significantly different from the control group, but it had a faster filtration rate. The absolute content of SFA and MUFA in crude oil, degummed oil, deacidified oil, and bleached oil had no significant difference. Increasing from (117.42±0.23) mg/g and (65.20±2.31) mg/g to (128.97±0.86) mg/g and (68.62±1.59) mg/g, the absolute content of EPA and DHA in bleached oil increased significantly. Conclusion: Magnesium silicate is an effective filter aid and has adsorption effect. Its combination with activated clay can ensure the decolorization effect of fish oil. Additionally, it can solve the problem of blocking the filter cake of separating the decolorizing agent and fish oil by the plate and frame filter press. The mixed decolorizing agent has the advantages of low oil absorption, high decolorization efficiency, and fast filtration speed.